World Economic Situation and Prospects 2022 - United Nations Department of Economic; Social Affairs (United Nations, 2022)
This is the United Nations definitive report on the state of the world economy, providing global and regional economic outlook for 2022 and 2023. The World Economic Situation and Prospects 2022 will examine the recovery of the global economy from the COVID-19 pandemic. In addition to presenting the latest UN growth forecasts, the report will provide a comprehensive assessment of economic developments, risk factors, and policy challenges. This year’s thematic chapter will discuss the macroeconomic and distributional consequences of monetary policy, with particular focus on unconventional measures such as quantitative easing (QE).